Geontologies : a requiem to late liberalism - Povinelli, Elizabeth A. (Duke University Press, 2016)
Finding biopolitics unable to adequately reveal the mechanisms of power that govern contemporary life, Elizabeth A. Povinelli offers ""geontopower"" as a new theory of power that operates through the regulation of clear distinctions between life and nonlife.